A Comparison of Music Learning Outcomes in Secondary Education Curricula in Indonesia and Australia - Dharmawanputra, Budi; Wicaksono, Bayu Aji (Universitas Negeri Surabaya, 2025)
This article will examine a comparison of music learning outcomes in secondary education curricula between Indonesia (Merdeka Curriculum) and Australia (Version 8.4 Curriculum). The objective of this research is to analyze how each curriculum formulates music competencies, as well as to examine the differences in pedagogical and ideological orientations that underlie them. The methodological approach entails curriculum document analysis, supplemented by literature studies and a critical-constructive approach to learning outcomes. The findings of the analysis indicate that the Merdeka Curriculum places significant emphasis on the preservation of traditional music and the cultivation of character in accordance with the values of the Lima Cita Sila, or Five Core Principles, of the Student Profile. However, the curriculum dedicates less attention to fostering creative exploration, the integration of digital technology, and the promotion of cross-cultural understanding. Conversely, the Australian Curriculum adopts a more progressive and open approach through three primary domains: creating, performing and responding. This approach fosters creativity, reflection, and collaboration within a global context. However, it places relatively less explicit emphasis on the moral and character-building functions of the arts. The conclusion of this study underscores the significance of integrating the preservation of local culture with the cultivation of global competencies in music education. The recommendations are intended to enhance the curriculum, ensuring its holistic nature, technological foundation, inclusivity with regard to cultural diversity, and alignment with 21st-century learning requirements.